EXPLORING THE ROLE OF DIGITAL COOPERATIVE LEARNING IN ALLEVIATING STUDENT STRESS AND ENHANCING SLEEP QUALITY: A LITERATURE REVIEW - Rita Yulia Anggraini; Muhamad Uyun; Julius Julius; Yupi Anggriani (Jurnal Konseling Pendidikan Islam, 2026)
This study explores the role of Digital Cooperative Learning (DCL) in reducing student stress and improving sleep quality through a traditional literature review based on sources from the Scopus database. As students face increasing academic pressure and extended screen exposure, especially in the post-pandemic learning landscape, DCL emerges as a promising pedagogical strategy that integrates collaborative learning with digital platforms. Findings indicate that DCL enhances student engagement, motivation, and critical thinking while simultaneously creating socially supportive environments that alleviate stress. Furthermore, cooperative digital settings foster emotional well-being and can indirectly improve sleep patterns by reducing anxiety and academic overload. However, the implementation of DCL is challenged by limited access to digital infrastructure, disparities in digital literacy, and a lack of psychological support systems. Successful adoption requires well-prepared educators, inclusive learning designs, and institutional investment in mental health integration. The study concludes that DCL, when designed with attention to both technological and psychosocial dimensions, has the potential to be a holistic educational approach that supports academic achievement and student wellness in the 21st-century digital classroom.